Lithium ion battery electrolyte and application thereof

By using carbodiimide-like cyclic compounds in the lithium-ion battery electrolyte, a dense interface mask is formed and reactive oxygen species is neutralized, and the problem of thermal runaway in the charging and discharging of lithium-ion batteries is solved, and safety performance and high-temperature storage capabilities are improved.

CN119542534AActive Publication Date: 2025-02-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411697217.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium-ion batteries, the oxygen release reaction is intensified due to the phase change of the positive electrode active material, which causes the risk of heat loss and affects safety performance.

Method used

A lithium-ion battery electrolyte containing a carbodiimide-based cyclic compound is used. The electrolyte is oxidized and decomposed on the electrode surface to form a dense interface film and has the ability to neutralize reactive oxygen species to prevent thermal runaway reactions.

Benefits of technology

It effectively solves the thermal runaway problem caused by reactive oxygen generated by the phase transition of the positive electrode active material, broadens the safe use window of lithium batteries, and improves high-temperature storage and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154054150000021
    Figure BDA0005154054150000021
  • Figure BDA0005154054150000032
    Figure BDA0005154054150000032
  • Figure BDA0005154054150000041
    Figure BDA0005154054150000041
Patent Text Reader

Abstract

The invention provides a lithium ion battery electrolyte and application thereof. The electrolyte comprises: a non-aqueous solvent; a lithium salt; and an additive, the additive comprises a first additive, and the first additive comprises a carbodiimide cyclic compound. According to the lithium ion battery electrolyte and the application thereof provided by the invention, the high-temperature storage and safety performance of the lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art

[0002] Lithium-ion batteries have developed rapidly in the fields of electric vehicles, power tools, and electric bicycles, occupying a large market share. With the widespread application of lithium-ion batteries, consumers have experienced many conveniences while putting forward higher requirements for the safety of lithium-ion batteries. Generally, the positive electrode active material of lithium-ion batteries with higher energy density is nickel-cobalt-manganese ternary material (NCM). During the charging and discharging process, the volume of the lattice in the layered structure of the ternary positive electrode active material expands and contracts, and its oxygen release reaction also continues to intensify. This will inevitably produce the safety risk of thermal runaway caused by oxygen, which will bring everyone a sense of safety anxiety in use, and further improvement and solution are urgently needed. Summary of the invention

[0003] The present invention provides a lithium ion battery electrolyte and application thereof. The lithium ion battery electrolyte and application thereof provided by the present invention can improve the high temperature storage and safety performance of the lithium ion battery.

[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:

[0005] Non-aqueous solvents;

[0006] lithium salts; and

[0007] The additive comprises a first additive, wherein the first additive comprises a carbodiimide cyclic compound.

[0008] In one embodiment of the present invention, the carbodiimide cyclic compound is selected from compounds having any structure of Formula I to Formula IV:

[0009]

[0010] wherein n1-n8 are each independently an integer of 0-3, X and Y are each independently selected from any one of P, As, S or Se atoms, Z is selected from any one of O, S or Se atoms, R1, R2, R3 and R4 are each independently selected from H, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6 Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12Aryl, C 6~12 Heteroaryl, carbonyl or C 2~6 Any one or a combination of ester groups.

[0011] In one embodiment of the present invention, at least one of X and Y includes any one of P, S or Se, and Z includes at least one of O or S element atoms.

[0012] In one embodiment of the present invention, the carbodiimide cyclic compound is selected from at least one or more combinations of the following compounds:

[0013]

[0014] In compound B, n3 is an integer of 0-3.

[0015] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.1 wt % to 15 wt %.

[0016] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.5 wt % to 5 wt %.

[0017] In one embodiment of the present invention, the additive further includes a second additive, and the second additive is selected from at least one or more combinations of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methanedisulfonic acid methylene ester, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium difluorophosphate or vinyl sulfate, and the content of the second additive in the electrolyte is 0.1wt% to 3wt%.

[0018] In one embodiment of the present invention, the non-aqueous solvent is selected from at least one or more combinations of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.

[0019] In one embodiment of the present invention, the lithium salt is selected from one or more combinations of lithium hexafluorophosphate, lithium bis(trifluoromethyl)sulfonyl imide or lithium bis(trifluoromethyl)sulfonyl imide, and the concentration of the lithium salt in the electrolyte is 0.3 mol / L to 2 mol / L.

[0020] The present invention also provides a lithium ion battery, comprising:

[0021] Positive electrode;

[0022] Negative electrode;

[0023] A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet;

[0024] The electrolyte is the lithium-ion battery electrolyte mentioned above.

[0025] In one embodiment of the present invention, the positive electrode plate and / or the separator includes a first additive.

[0026] The present invention also provides an electronic device, comprising the lithium-ion battery described above.

[0027] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. Through the first additive, it can be oxidized and decomposed on the electrode surface, generate a ring-opening polymerization reaction, and form a complete, dense and uniform passivation film. At the same time, it has a certain ability to neutralize active oxygen. Under overcharge conditions, the interface film formed by the carbodiimide cyclic compound will immediately block the active oxygen reaction, which can effectively solve the lithium battery safety problems such as the rapid release of a large amount of heat by the interface side reaction caused by the phase change of the positive electrode active material. It can greatly reduce the release of a large amount of heat by further oxidation of solvents such as ethylene carbonate in the electrolyte due to the large amount of active oxygen released by the positive electrode active material, effectively prevent the thermal release reaction of the lithium-ion battery from staying at the thermal runaway trigger temperature T2 stage, and broaden the safe use window of the lithium battery. At the same time, it will not affect the fast charging, rate performance and other dynamics of the lithium battery. It can improve the integrity and dense layer of the interface film, and improve the high-temperature storage and safety performance of the lithium-ion battery. DETAILED DESCRIPTION

[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0029] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0030] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] The present invention provides a lithium ion battery electrolyte, comprising at least a non-aqueous solvent, a lithium salt and an additive, wherein the additive comprises a first additive, the first additive comprises a carbodiimide cyclic compound, and the carbodiimide cyclic compound is selected from a compound having any structure of Formula I to Formula IV:

[0032]

[0033] wherein n1-n8 are each independently an integer of 0-3, X and Y are each independently selected from any one of P, As, S or Se atoms, Z is selected from any one of O, S or Se atoms, R1, R2, R3 and R4 are each independently selected from H, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6 Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12 Aryl, C 6~12 Heteroaryl, carbonyl or C 2~6 Any one or a combination of several of the ester groups, etc. Among them, the film-forming potential of carbodiimide cyclic compounds is low, and they are easier to oxidize and decompose on the electrode surface, generate ring-opening polymerization reactions, and form a complete, dense and uniform passivation film. The carbodiimide polar functional group in its molecular formula is continuously reduced under high voltage. At the same time, the compound has a certain ability to neutralize active oxygen. Under overcharge conditions, the interface film formed by the carbodiimide cyclic compound will immediately block the active oxygen reaction, which can effectively solve the lithium battery safety problems such as the rapid release of a large amount of heat by the interface side reaction caused by the phase change of the positive active material under the conditions of high potential overcharge and high temperature thermal triggering of NCM ternary layered positive electrode active materials. It can greatly reduce the release of a large amount of heat due to the further oxidation of solvents such as ethylene carbonate in the electrolyte by the large amount of active oxygen released by the positive active material, effectively prevent the thermal release reaction of lithium-ion batteries from staying at the thermal runaway trigger temperature T2 stage, and broaden the safe use window of lithium batteries. At the same time, it will not affect the fast charging and rate performance of lithium batteries.

[0034] In one embodiment of the present invention, in the carbodiimide cyclic compound, at least one of X and Y includes any one of P, S or Se, and Z includes at least one of O or S atoms. In one embodiment of the present invention, at least one of X, Y and Z includes S atoms. The carbodiimide cyclic compound is selected from at least one or more combinations of the following compounds:

[0035]

[0036]

[0037] etc., wherein in compound B, n3 is an integer of 0-3. Among them, the cyclic compound containing S is easier to obtain electron ring-opening polymerization to form a film, and the formed interface film has strong flexibility and a relatively stable spatial structure, and can chemically neutralize a large amount of active oxygen generated by overcharging. After film formation, the film layer has more sulfonate or sulfate inorganic components, and has stronger ion conductivity, which can further improve the performance of lithium-ion batteries.

[0038] In another embodiment of the present invention, in the carbodiimide cyclic compound, the compound containing one acyl group and / or two acyl groups in the ring, for example, the carbodiimide cyclic compound is selected from wait.

[0039] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.1wt% to 15wt%, and for example, 0.5wt% to 5wt%. If the content of the first additive is too low, a dense interface film cannot be formed, resulting in a low pass rate of the high-voltage overcharge test of the lithium-ion battery, and the safety improvement of the lithium-ion battery is not obvious. As the content of the first additive increases, a dense interface film can be formed, and all high-voltage overcharge tests of the lithium-ion battery are passed, but the high-temperature storage capacity and high-temperature storage gas production of the lithium-ion battery are not further improved as the content is further increased. Considering cost factors, the upper limit of the content of the first additive is controlled.

[0040] In one embodiment of the present invention, the additive further includes a second additive, the second additive is selected from at least one or more combinations of film-forming additives such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 2,4-butanesultone (2,4-Butanesultone), methylene methanedisulfonate (MMDS), lithium difluoro oxalate borate (LiODFB), lithium dioxalate borate (LiBOB), lithium difluorobis oxalate phosphate (LiDFOB), lithium tetrafluoro oxalate phosphate (LiOTFP), lithium difluoro phosphate (LiDFP) or vinyl sulfate (1,3,2-Dioxathiolane 2,2-dioxide, DTD), and the content of the second additive in the electrolyte is 0.1wt% to 5wt%. In one embodiment of the present invention, the second additive is, for example, selected from any one or a combination of 0.02wt% to 5wt% of vinylene carbonate, 0.02wt% to 3wt% of fluoroethylene carbonate, 0.02wt% to 3wt% of 1,3-propane sultone, 0.02wt% to 3wt% of 1,3-propylene sultone, 0.02wt% to 3wt% of 2,4-butane sultone, 0.02wt% to 3wt% of methylene disulfonate, 0.02wt% to 3wt% of lithium difluorooxalatoborate, 0.02wt% to 3wt% of lithium dioxalatoborate, 0.02wt% to 1wt% of lithium difluorophosphate, 0.02wt% to 3wt% of lithium difluorobisoxalatophosphate, or 0.02wt% to 3wt% of vinyl sulfate. The second additive can cooperate with the first additive to further improve the integrity and compactness of the interface film, thereby improving the cycle performance and safety performance of the lithium-ion battery.

[0041] In one embodiment of the present invention, the lithium salt is selected from any one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethyl)sulfonylimide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6) and lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) or lithium difluoro(oxalatoborate), and the concentration of the lithium salt in the electrolyte is 0.1 mol / L to 2 mol / L, for example, 0.5 mol / L to 1.3 mol / L.

[0042] In one embodiment of the present invention, the non-aqueous solvent includes, for example, at least one or more combinations of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl acetate (EA), methyl acetate (MA), ethyl formate (MEE), propyl formate (PF), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP) or n-propyl propionate (PP), and the mass content of the non-aqueous solvent in the electrolyte is 70wt% to 85wt%.

[0043] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with an inert gas atmosphere such as argon gas with a moisture content and an oxygen content less than or equal to 0.1 ppm, the non-aqueous solvent is mixed uniformly according to the mass ratio, and the fully dried lithium salt is added to the non-aqueous solvent, and an additive is added to prepare a lithium ion battery electrolyte. The content described in this application is the weight percentage calculated based on the total weight of the electrolyte.

[0044] The present invention proposes a lithium-ion battery, which includes a shell and a bare cell arranged in the shell, and the bare cell includes a positive electrode sheet, a separator and a negative electrode sheet. The separator is placed between the positive and negative electrode sheets to prevent the positive and negative electrodes from short-circuiting, so that lithium ions can pass through. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and a multi-layer laminate is obtained by winding or folding, and is loaded into a battery shell as a bare cell. Finally, an electrolyte is injected into the shell once or multiple times so that the bare cell is completely immersed in the electrolyte. The electrolyte is, for example, selected from the above-mentioned electrolytes, and plays a role in conducting ions between the positive and negative electrode sheets. In one embodiment of the present invention, the lithium-ion battery is, for example, a secondary battery, and the secondary battery is, for example, a soft-pack battery, a square shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type of lithium-ion battery.

[0045] In an embodiment of the present invention, the positive electrode plate includes a positive electrode current collector and a positive electrode active layer coated at least on one surface of the positive electrode current collector. Among them, the positive electrode current collector is, for example, a metal foil or a composite current collector, etc. The metal foil is, for example, a foil material formed after surface treatment of nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, silver alloy, or stainless steel, etc. The composite current collector, for example, includes a polymer material base layer and a metal layer formed at least on one surface of the polymer material base layer. Among them, the material of the polymer material base layer is, for example, selected from at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE), etc. The material of the metal layer is, for example, selected from at least one of aluminum, aluminum alloy, nickel, nickel alloy, silver, silver alloy, or titanium alloy, etc.

[0046] In an embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder, a conductive agent, etc. Among them, the positive electrode active material, for example, includes but is not limited to nickel cobalt manganese ternary material. The general formula of the nickel cobalt manganese ternary material is LiNi a Co b Mn 1-a-b O2, where the value ranges of a and b are 0 < a < 1 and 0 < b < 1. The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene terpolymer (ETFE), vinylidene fluoride - hexafluoropropylene - tetrafluoroethylene terpolymer (TFE - HFP - VDF), or tetrafluoroethylene - hexafluoropropylene copolymer (FEP), etc. The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P), acetylene black, or Ketjen black, etc. In the positive electrode active layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is, for example, (90 - 98):(1 - 5):(1 - 5).

[0047] In an embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1O2, the binder is selected from polyvinylidene fluoride, the conductive agent is selected from acetylene black, the positive electrode active material, the conductive agent and the binder are mixed, for example, in a mass ratio of 96.5:1.5:2, and then an organic solvent is added. Stirring the system is uniform under the action of a vacuum mixer to obtain a positive electrode slurry. Among them, the organic solvent is selected from N-methylpyrrolidone (NMP), for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing, trimming, cutting and striping. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.

[0048] In one embodiment of the present invention, the positive electrode plate, for example, includes a first additive. Specifically, the positive electrode active material, the conductive agent, the binder and the first additive are mixed, for example, in a mass ratio of 97.3:1.5:1:0.2, and then an organic solvent is added. The mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The organic solvent is selected from N-methylpyrrolidone, for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode plate is obtained through processes such as cold pressing, trimming, cutting and stripping. The first additive is added to the positive electrode plate, and the effect of improving the safety performance of the lithium-ion battery is similar to the effect of adding the first additive to the electrolyte.

[0049] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, a metal foil or a composite current collector, the metal foil is, for example, a copper foil, and the composite current collector includes, for example, a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The material of the polymer material base layer is, for example, selected from at least one of PP, PET, PBT, PS or PE, and the material of the metal layer is, for example, selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.

[0050] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener. Among them, the negative electrode active material includes, for example, any one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials or lithium titanate. Among them, the silicon-based material includes, for example, one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites or silicon alloys, and the tin-based material includes, for example, one or more of elemental tin, sacrificial oxygen compounds or tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0051] In one embodiment of the present invention, the binder is selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic amide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS), etc. The thickener is selected from carboxymethyl cellulose sodium (CMC-Na), etc. The conductive agent is selected from any one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers, etc. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).

[0052] In one embodiment of the present invention, the negative electrode active material is selected from graphite and silicon-carbon composite, and the mass ratio of silicon-carbon composite to graphite is, for example, 95:5 to 80:20, the conductive agent is selected from conductive carbon black, the thickener is selected from sodium carboxymethyl cellulose, and the binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, the conductive agent, the thickener and the binder are mixed, for example, in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing, trimming, cutting and stripping. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.

[0053] In one embodiment of the present invention, the diaphragm is, for example, a ceramic diaphragm, a polymer diaphragm, a non-woven fabric or an inorganic-organic composite diaphragm, including but not limited to a single-layer polypropylene film (Polypropylene, PP), a single-layer polyethylene film (Polyethylene, PE), a double-layer PP / PE film, a double-layer PP / PP film and a three-layer PP / PE / PP film.

[0054] In one embodiment of the present invention, the diaphragm includes a first additive. Specifically, a preset mass of the first additive is dissolved in a suspension containing ceramic particles and a PVDF binder and stirred, and then sprayed on one or both sides of a PE or PP polymer diaphragm. After drying, a composite layer is formed. The ceramic particles are, for example, aluminum oxide, the thickness of the composite layer is, for example, 2 μm to 4 μm, and the content of the first additive in the composite layer is, for example, 25 wt% to 35 wt%. The formed diaphragm, positive / negative electrode sheets, and electrolyte are made into a lithium-ion battery, which can also improve the safety performance of the lithium-ion battery.

[0055] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare cell is obtained by winding or stacking. The bare cell is placed in a shell, dried, injected with electrolyte, and sealed, and at least vacuum packaging, standing, forming, and shaping are performed to obtain a lithium-ion battery.

[0056] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0057] Example 1

[0058] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC were mixed at a mass ratio of 3:5:2 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide were added to the mixed solvent, the concentration of lithium hexafluorophosphate was 1mol / L, and the concentration of lithium bis(fluorosulfonyl)imide was 0.13mol / L. Then 1wt% of 1,3-propane sultone, 1wt% of vinyl sulfate and 0.1wt% of compound A were added thereto and mixed to obtain an electrolyte.

[0059] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 96.5:1.5:2, and NMP was added. The mixture was stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on aluminum foil, and then dried at room temperature and transferred to an oven for drying. The positive electrode sheet was obtained through cold pressing, trimming, cutting and slitting.

[0060] Preparation of negative electrode sheets: the negative electrode active materials are graphite and silicon-carbon composites, and the mass ratio of the silicon-carbon composite to graphite is, for example, 85:15. The negative electrode active materials, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing, trimming, cutting and slitting processes, a negative electrode sheet is obtained.

[0061] Selection of diaphragm: Polyethylene with a thickness of 9 μm is used as the base membrane.

[0062] Preparation of battery: The positive electrode sheet, separator, and negative electrode sheet are wound in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a bare cell. Then the bare cell is placed in an aluminum-plastic film, dried, injected with electrolyte, and sealed. After at least vacuum packaging, standing, formation, and shaping processes, a lithium-ion battery is obtained.

[0063] Example 2

[0064] In the electrolyte, the content of compound A is 0.25 wt %, and the other steps are consistent with Example 1.

[0065] Example 3

[0066] In the electrolyte, the content of compound A is 0.5 wt %, and the other steps are consistent with Example 1.

[0067] Example 4

[0068] In the electrolyte, the content of compound A is 1 wt %, and the other steps are consistent with Example 1.

[0069] Example 5

[0070] In the electrolyte, the content of compound A is 2.5 wt %, and the other steps are consistent with Example 1.

[0071] Example 6

[0072] In the electrolyte, the content of compound A is 5 wt %, and the other steps are consistent with Example 1.

[0073] Example 7

[0074] In the electrolyte, the content of compound A is 15 wt %, and the other steps are consistent with Example 1.

[0075] Example 8

[0076] In the electrolyte, compound A was replaced by compound B, and the content of compound B was 2.5 wt %. The other steps were consistent with Example 1.

[0077] Example 9

[0078] In the electrolyte, compound A was replaced by compound D, and the content of compound D was 2.5 wt %. The other steps were consistent with Example 1.

[0079] Example 10

[0080] In the electrolyte, compound A was replaced by compound E, and the content of compound E was 2.5 wt %. Other steps were consistent with Example 1.

[0081] Embodiment 11

[0082] In the electrolyte, compound A was replaced by compound F, and the content of compound F was 2.5 wt %. Other steps were consistent with Example 1.

[0083] Example 12

[0084] In the electrolyte, compound A was replaced by compound H, and the content of compound H was 2.5 wt %. The other steps were consistent with Example 1.

[0085] Example 13

[0086] In the electrolyte, the first additive is compound A and compound B, and the content of compound A is 1.5wt%, and the content of compound B is 1wt%. Other steps are consistent with Example 1.

[0087] Embodiment 14

[0088] In the electrolyte, compound A was replaced by compound D and compound F, and the content of compound D was 1.5 wt %, and the content of compound F was 1 wt %. The other steps were consistent with Example 1.

[0089] Embodiment 15

[0090] In the electrolyte, all lithium salts are lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate is 1.13 mol / L. Compound A is replaced by compound D and compound E, and the content of compound D is 1.5 wt %, and the content of compound E is 1 wt %. The other steps are consistent with Example 1.

[0091] Example 16

[0092] In the electrolyte, the first additive is compound A and compound E, and the content of compound A is 2wt%, and the content of compound E is 0.5wt%. Other steps are consistent with Example 1.

[0093] Embodiment 17

[0094] In the electrolyte, compound A was replaced by compound B, and the content of compound B was 5 wt %. The other steps were consistent with Example 1.

[0095] Embodiment 18

[0096] In the electrolyte, compound A was replaced by compound E, and the content of compound E was 5 wt %. The other steps were consistent with Example 1.

[0097] Embodiment 19

[0098] In the electrolyte, compound A was replaced by compound E and compound F, and the content of compound E was 2.5 wt %, and the content of compound F was 2.5 wt %. The other steps were consistent with Example 1.

[0099] Embodiment 20

[0100] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC were mixed at a mass ratio of 3:5:2 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide were added to the mixed solvent, the concentration of lithium hexafluorophosphate was 1mol / L, and the concentration of lithium bis(fluorosulfonyl)imide was 0.13mol / L. Then 1wt% of 1,3-propane sultone and 1wt% of vinyl sulfate were added thereto and mixed to obtain an electrolyte.

[0101] Selection of diaphragm: Using polyethylene with a thickness of 9 μm as the base film, a preset mass of compound A is dissolved in a suspension containing aluminum oxide particles and a PVDF binder, stirred, and then sprayed on both sides of the polyethylene. After drying, a composite layer is formed. The ceramic particles are, for example, aluminum oxide, the thickness of the composite layer is 3 μm, and the content of compound A in the composite layer is 30%. The other steps are consistent with Example 1.

[0102] Embodiment 21

[0103] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC were mixed at a mass ratio of 3:5:2 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide were added to the mixed solvent, the concentration of lithium hexafluorophosphate was 1mol / L, and the concentration of lithium bis(fluorosulfonyl)imide was 0.13mol / L. Then 1wt% of 1,3-propane sultone and 1wt% of vinyl sulfate were added thereto and mixed to obtain an electrolyte.

[0104] Preparation of positive electrode: LiNi0.8 Co 0.1 Mn 0.1 O2, acetylene black, polyvinylidene fluoride and compound A are mixed in a mass ratio of 97.3:1.5:1:0.2, and NMP is added. The mixture is stirred in a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature. The positive electrode sheet is obtained through cold pressing, trimming, cutting and stripping. The other steps are consistent with those in Example 1.

[0105] Comparative Example 1

[0106] The electrolyte does not include the first additive, and the other steps remain the same as those in Example 1.

[0107] Comparative Example 2

[0108] The electrolyte does not include the first additive, and the other steps remain consistent with Example 15.

[0109] In the present invention, in Examples 1-21 and Comparative Examples 1-2, the components of the electrolyte in the lithium ion battery are shown in Table 1, and different electrolytes are used to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested. The test results are shown in Table 2.

[0110] In one embodiment of the present invention, the test method of low-temperature direct current resistance (DCR) test is as follows: at 25°C, charge the lithium-ion battery at a constant current of 1 / 3C to 4.25V, and then charge at a constant voltage to a current of 0.05C. Then discharge the battery at a constant current of 1 / 3C to 2.8V. Repeat the above charging steps, and record the second charging capacity as C0. Discharge the battery at a constant current of 1 / 3C to (50%*C0). Then place the battery at -20°C and record the initial voltage as U0. Discharge the battery at a constant current of 1C for 30s, and record the terminal voltage as U1. Low-temperature DCR = (U0-U1) / (C0*1).

[0111] In one embodiment of the present invention, the test method of the room temperature DCR test is as follows: At 25°C, the lithium-ion battery is charged to 4.25V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.8V at a constant current of 1 / 3C. Repeat the above charging steps, and the second charging capacity is recorded as C1. The battery is discharged to (50%*C1) at a constant current of 1 / 3C, and the initial voltage is recorded as U2. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U3. Room temperature DCR = (U2-U3) / (C1*1).

[0112] In one embodiment of the present invention, the test method of the high temperature storage test is as follows: the lithium-ion battery is stored at 60°C for 30 days (30D). The battery is then placed at 25°C and discharged to 2.8V at a 1 / 3C constant current, and then the battery is charged to 4.25V at a 1 / 3C constant current, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.8V at a 1 / 3C constant current, and the discharge capacity is recorded as C2. The capacity recovery rate is (C2 / C1)*100%. Repeat the above charging steps, and the second charging capacity is recorded as C3. The battery is discharged to (50%*C3) at a 1 / 3C constant current, and the initial voltage is recorded as U4. The battery is discharged at a 1C constant current for 30s, and the terminal voltage is recorded as U5. DCR = (U4-U5) / (C3*1). DCR growth rate = (DCR after storage for 30 days-initial DCR) / initial DCR*100%. At the same time, record the volume V1 of the lithium-ion battery at 25°C before storage and the volume V2 at room temperature after storage at 60°C for 30 days. Volume expansion rate = (V2-V1) / V1*100%.

[0113] In one embodiment of the present invention, the overcharge test is to charge the lithium-ion batteries of Examples 1 to 21 and Comparative Examples 1 to 2 at 25°C at a constant current of 1 / 3C to 4.25V, and then charge at a constant voltage to a current of 0.05C. Then discharge the battery at a constant current of 1 / 3C to 2.8V. The first discharge capacity of the battery is recorded, and then the lithium-ion battery is charged at a current of 0.33C0 for 236.4min or constant current to a voltage of 4.89V, and placed in an explosion-proof box in situ to observe for 1h whether the battery cell has an explosion-proof valve opening or a fire triggering thermal runaway, etc. If not, the test is passed.

[0114] Table 1. Components of the electrolyte in Examples 1-21 and Comparative Examples 1-2

[0115]

[0116] Table 2. Performance of lithium-ion batteries in Examples 1-21 and Comparative Examples 1-2

[0117]

[0118] Please refer to Table 1 and Table 2. By comparing Examples 1-7 and Comparative Example 1, it can be seen that when the first additive is not added to the electrolyte, the high-temperature storage volume expansion rate of the lithium-ion battery is large, and the overcharge test fails, indicating that the safety of the lithium-ion battery is poor. As the content of the first additive increases, the high-temperature storage volume expansion rate can be reduced, and the pass rate of the high-voltage overcharge test of the lithium-ion battery increases until all the tests are passed. It shows that as the content of the first additive increases, a dense interface film can be formed, and the carbodiimide polar functional group in the molecular formula of the first additive is continuously reduced under high voltage, and has a certain ability to neutralize active oxygen. Under overcharge conditions, the interface film formed by the first additive can block the active oxygen reaction in the first time, thereby improving the safety performance of lithium ions. However, the high-temperature storage capacity and high-temperature storage gas production of lithium-ion batteries have not been further improved with the further increase in content. Considering cost factors, the upper limit of the content of the first additive is controlled. However, the first additive also increases the thickness of the interface film to a certain extent, resulting in a slight increase in DC impedance.

[0119] Please refer to Table 1 and Table 2. By comparing Examples 5 and 8-16, and Examples 6 and 17-19, it can be seen that when the content of the first additive is the same, when the first additive selects different compounds or different compound combinations, the high-temperature storage and high-voltage overcharge pass rates of the lithium-ion battery are at the same level, indicating that first additives with different structures can improve the safety performance and high-temperature storage performance of lithium-ion batteries. Among them, in Examples 11 and 12, in Compounds F and H, the heterocyclic functional groups at both ends of the carbodiimide are single, with only one sulfone functional group, and the degree of polymerization is relatively low, and its ability of ring-opening polymerization is reduced, and the mechanical properties of the formed interface film are poor, resulting in slightly poor improvement in the high-temperature storage gas production of the formed lithium-ion battery.

[0120] Please refer to Table 1 and Table 2. By comparing Examples 2 to 6 and 20-21, it can be seen that when the first additive is applied to the diaphragm or the positive electrode plate, especially when applied to the diaphragm, the improvement effect is limited and the high voltage overcharge cannot be fully passed. When applied to the positive electrode plate, the high voltage overcharge can be fully passed, and the safety performance and high temperature storage performance of the lithium-ion battery are better. In summary, when the first additive is an electrolyte additive and a positive electrode plate additive, the high temperature storage improvement effect and high voltage overcharge pass rate of the lithium-ion battery are higher, and its corresponding processability is also stronger.

[0121] Please refer to Table 1. By comparing Example 15 and Comparative Example 2, it can be seen that when the electrolyte does not contain a stable lithium salt LiFSI, by adding the first additive, the high voltage overcharge pass rate is increased, the high temperature storage performance is improved, and the performance of the lithium-ion battery can also be improved.

[0122] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0123] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. Through the first additive, it can be oxidized and decomposed on the electrode surface, generate a ring-opening polymerization reaction, and form a complete, dense and uniform passivation film. At the same time, it has a certain ability to neutralize active oxygen. Under overcharge conditions, the interface film formed by the carbodiimide cyclic compound will immediately block the active oxygen reaction, which can effectively solve the lithium battery safety problems such as the rapid release of a large amount of heat by the interface side reaction caused by the phase change of the positive electrode active material. It can greatly reduce the release of a large amount of heat by further oxidation of solvents such as ethylene carbonate in the electrolyte due to the large amount of active oxygen released by the positive electrode active material, effectively prevent the thermal release reaction of the lithium-ion battery from staying at the thermal runaway trigger temperature T2 stage, and broaden the safe use window of the lithium battery. At the same time, it will not affect the fast charging, rate performance and other dynamics of the lithium battery. It can improve the integrity and dense layer of the interface film, and improve the high-temperature storage and safety performance of the lithium-ion battery.

[0124] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0125] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Non-aqueous solvents; lithium salts; and The additive comprises a first additive, wherein the first additive comprises a carbodiimide cyclic compound.

2. The lithium ion battery electrolyte according to claim 1, characterized in that: The carbodiimide cyclic compound is selected from compounds having any structure of Formula I to Formula IV: wherein n1-n8 are each independently an integer of 0-3, X and Y are each independently selected from any one of P, As, S or Se atoms, Z is selected from any one of O, S or Se atoms, R1, R2, R3 and R4 are each independently selected from H, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6 Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12 Aryl, C 6~12 Heteroaryl, carbonyl or C 2~6 Any one or a combination of ester groups.

3. The lithium ion battery electrolyte according to claim 2, characterized in that: At least one of X and Y includes any one of P, S or Se, and Z includes at least one of O or S element atoms.

4. The lithium ion battery electrolyte according to claim 2, characterized in that: The carbodiimide cyclic compound is selected from at least one or more combinations of the following compounds: In compound B, n3 is an integer of 0-3.

5. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.1 wt% to 15 wt%.

6. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.5 wt % to 5 wt %.

7. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a second additive, which is selected from at least one or more combinations of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorobisoxalatephosphate, lithium tetrafluorooxalatephosphate, lithium difluorophosphate or vinyl sulfate, and the content of the second additive in the electrolyte is 0.1wt% to 3wt%.

8. The lithium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent is selected from at least one or more combinations of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.

9. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is selected from one or more combinations of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethyl)sulfonyl imide, and the concentration of the lithium salt in the electrolyte is 0.3 mol / L to 2 mol / L.

10. A lithium ion battery, characterized in that: include: Positive electrode; Negative electrode; A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet; An electrolyte, wherein the electrolyte is selected from the lithium-ion battery electrolyte according to any one of claims 1 to 9.

11. The lithium ion battery according to claim 10, characterized in that: The positive electrode sheet and / or the separator includes a first additive.

12. An electronic device, characterized in that: A lithium-ion battery comprising any one of claims 10-11.

Citation Information

Patent Citations

  • Lithium ion battery non-aqueous electrolyte and lithium ion battery

    CN113659205A

  • Electrolyte and battery comprising same

    CN116365030A

  • Non-aqueous electrolyte and lithium manganese iron phosphate battery

    CN116845354A

  • Slurry composition, and positive electrode and lithium secondary battery comprising same

    US20230387414A1